EXPLORING THE IMPLEMENTATION OF ONLINE LEARNING PROGRAM FROM THE PERSPECTIVE OF LEARNERS IN REMOTE AREA - Nisrina, Nisrina (Universitas Negeri Malang, 2021)
Abstract: This research is intended to explore the students who follow the online learning programzso called Recognition of Prior Learning in Remote Area. Qualitative descriptive method was conducted to gain the data the findings. After spread the questionnaire as instrument of the study, the result show that students’ motivation must be maintained after first meeting of the class, students’ autonomous learning does not activated automatically even the teachers use online learning platform; teachers’ instruction must be vividly stated that there are instruction that insist them to open the platform outside the learning period. Students’ English proficiency also seems do not show positive vibe. Stakeholder of the program are advised to do training on the lecturer before running the program in remote area; to mitigate the discrepancy of the learning system in platform used. Teachers are boosted to have a clear instruction to mitigate time and space constraint in learning activities.Keywords: , online learning, students’ perceptions